Laparoscopic vs open total gastrectomy for gastric cancer: a meta-analysis - Xiong, Jun-Jie; Nunes, Quentin M; Huang, Wei; Tan, Chun-Lu; Ke, Neng-Wen; Xie, Si-Ming; Ran, Xun; Zhang, Hao; Chen, Yong-Hua; Liu, Xu-Bao (World journal of gastroenterology : WJG, 2013)
To conduct a meta-analysis comparing laparoscopic total gastrectomy (LTG) with open total gastrectomy (OTG) for the treatment of gastric cancer. Major databases such as Medline (PubMed), Embase, Academic Search Premier (EBSCO), Science Citation Index Expanded and the Cochrane Central Register of Controlled Trials (CENTRAL) in The Cochrane Library were searched for studies comparing LTG and OTG from January 1994 to May 2013. Evaluated endpoints were operative, postoperative and oncological outcomes. Operative outcomes included operative time and intraoperative blood loss. Postoperative recovery included time to first ﬂatus, time to first oral intake, hospital stay and analgesics use. Postoperative complications comprised morbidity, anastomotic leakage, anastomotic stenosis, ileus, bleeding, abdominal abscess, wound problems and mortality. Oncological outcomes included positive resection margins, number of retrieved lymph nodes, and proximal and distal resection margins. The pooled effect was calculated using either a fixed effects or a random effects model. Fifteen non-randomized comparative studies with 2022 patients were included (LTG - 811, OTG - 1211). Both groups had similar short-term oncological outcomes, analgesic use (WMD -0.09; 95%CI: -2.39-2.20; P = 0.94) and mortality (OR = 0.74; 95%CI: 0.24-2.31; P = 0.61). However, LTG was associated with a lower intraoperative blood loss (WMD -201.19 mL; 95%CI: -296.50--105.87 mL; P < 0.0001) and overall complication rate (OR = 0.73; 95%CI: 0.57-0.92; P = 0.009); fewer wound-related complications (OR = 0.39; 95%CI: 0.21-0.72; P = 0.002); a quicker recovery of gastrointestinal motility with shorter time to ﬁrst ﬂatus (WMD -0.82; 95%CI: -1.18--0.45; P < 0.0001) and oral intake (WMD -1.30; 95%CI: -1.84--0.75; P < 0.00001); and a shorter hospital stay (WMD -3.55; 95%CI: -5.13--1.96; P < 0.0001), albeit with a longer operation time (WMD 48.25 min; 95%CI: 31.15-65.35; P < 0.00001), as compared with OTG. LTG is safe and effective, and may offer some advantages over OTG in the treatment of gastric cancer.